A role of mass medias is in forming for the students of healthy way of life in the Peoples Republic of China. - Ван Сюємань Van Xuemang (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to define attitude of students of Peoples Republic of China toward the role of mass medias in forming of healthy way of life. Material and methods: analysis of literary sources and documents, methods of analysis of the systems, questioning (a questionnaire is 90 students of Peoples Republic of China), methods of the mathematical processing of data. Results: students consider television the most meaningful in society medium of communication, that mark 40% respondentiv, farther is the World global network the Internet (31%), printing editions (20%), radios (9%), most popularity is used by televisional and the Internet of translation of competitions in the command types of sport (31%), competitions on track-and-field (19%), and also child’s competitions (17%). Conclusions: 72% students consider that the mass-media are able to form in a population positive attitude toward a physical culture, 49% respondents consider here, that the mass-media can explain a population to engaged in physical exercises, and 51% – that does not can.